Palaeodictyopterida - Prokop, Jakub; Engel, Michael S (Current biology, 2019)
Jakub Prokop and Michael Engel introduce palaeodictyopterids, a very diverse extinct lineage of insects.
Keywords: Insecta; zkameněliny; Biological Evolution; Animals; hmyz; zvířata; biologická evoluce; Fossils